TPACK and its Contribution to Develop Differentiated Learning in Elementary School - Mardati, Asih; Maryani, Ika; Suyatno, Suyatno (Profesi Pendidikan Dasar, 2024)
In recent years, the integration of technology in education has become increasingly vital for enhancing teaching and learning processes. This study utilized a correlational research methodology, focusing on elementary schools in the city of Yogyakarta that have adopted an independent curriculum. A sample of 20 teachers was selected using stratified random sampling. Data collection was conducted through questionnaires, with both questionnaire grids and sheets employed. The data analysis was performed using descriptive and inferential statistics. The research findings indicate positive values for various components of Technological Pedagogical Content Knowledge (TPACK): TPACK (0.894), Content Knowledge (CK) (0.783), Technological Knowledge (TK) (0.782), Pedagogical Knowledge (PK) (0.869), Pedagogical Content Knowledge (PCK) (0.835), Technological Content Knowledge (TCK) (0.866), and Technological Pedagogical Knowledge (TPK) (0.861). These results suggest that a teacher's TPACK significantly influences and is closely associated with their ability to develop differentiated learning strategies. These findings imply that professional development programs aimed at enhancing teachers' TPACK could play a crucial role in improving their effectiveness in implementing differentiated learning strategies.